Farmer-to-farmer training adopted by 86 organizations serving 352,000 farmers in Eastern Africa improves dairy farmers' knowledge, productivity and revenues - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
Since 2012, FTA and PIM have supported efforts by ICRAF and partners to implement the volunteer farmer trainer approach in Eastern Africa. As of 2018, 86 organizations across Eastern Africa have adopted the volunteer farmer trainer approach. These organizations work with 17,600 volunteer farmer trainers and serve 352,000 farmers. An impact evaluation found that the use of this approach improved farmers? knowledge of dairy practices as well as dairy productivity and revenues in Uganda's Busoga region.